2019
DOI: 10.1002/tox.22738
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 mediated MAPK signaling pathway promotes collagen formation induced by Nano NiO in A549 cells

Abstract: Nickel oxide nanoparticles (Nano NiO) could induce pulmonary fibrosis, however, the mechanisms are still unknown. The aim of the present study was to explore the roles of transforming growth factor‐β1 (TGF‐β1), mitogen‐activated protein kinase (MAPK) pathway and MMPs/TIMPs balance in Nano NiO‐induced pulmonary fibrosis. For that purpose, we first established Nano NiO‐induced human lung adenocarcinoma epithelial cells (A549 cells) model of collagen excessive formation through detecting the levels of hydroxyprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…TGF‐β1 plays crucial roles in the nano materials‐induced lung injury including inflammatory response, collagen deposition, and pulmonary fibrosis 17,25 . Our previous study shown that the increasing TGF‐β1 concentration was observed in rats and A549 cells exposed to nano NiO 4,19 . Current results found TGF‐β1 was activated by nano NiO in A549 cells, furtherly verified the role of TGF‐β1.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…TGF‐β1 plays crucial roles in the nano materials‐induced lung injury including inflammatory response, collagen deposition, and pulmonary fibrosis 17,25 . Our previous study shown that the increasing TGF‐β1 concentration was observed in rats and A549 cells exposed to nano NiO 4,19 . Current results found TGF‐β1 was activated by nano NiO in A549 cells, furtherly verified the role of TGF‐β1.…”
Section: Discussionsupporting
confidence: 65%
“…17,25 Our previous study shown that the increasing TGF-β1 concentration was observed in rats and A549 cells exposed to nano NiO. 4,19 Current results found TGF-β1 was activated by nano NiO in A549 cells, furtherly verified the role of TGF-β1. Smad3 is a key substrate of TGF-βR1 kinase and mediates signal transduction in the cell biology.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, the contribution of p38 and JNK pathways for TGF-β to activate renal brosis has been addressed [24,25]. Together with our current ndings, the p38 and JNK inhibitors may provide a potential target in the treatment of GO [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 75%
“…Yu et al [22] proposed that TGF-β1 activated hepatic stellate cells via p38 and ERK pathways in liver brosis. Tian et al [23] reported the correlation of TGF-β1dependent p38 and ERK pathways with nickel oxide nanoparticle-induced pulmonary brosis.…”
Section: Discussionmentioning
confidence: 99%